The transatlantic book club : a novel - Hayes-McCoy, Felicity (Harper, an imprint of HarperCollinsPublishers, 2020)
Setting up a transatlantic Skype book club to stay in touch with her recently widowed grandmother on Ireland's Finfarran Peninsula, Cassie uncovers tragic family secrets that reveal unexpected truths about her grandmother's marriage.